2011
DOI: 10.1021/np100736y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Oncogenic Transcription Factor AP-1 from Podocarpus latifolius

Abstract: An activator protein-1 (AP-1) based bioassay guided phytochemical investigation on Podocarpus latifolius led to the isolation of three new sempervirol type diterpenes, cycloinumakiol (1), inumakal (2), and inumakoic acid (3) along with three known norditerpenes (4-6). Compounds 4 and 6 were responsible for the observed bioactivity.Carcinogenesis, the process of transforming normal cells into cancer cells, is a multistage process of initiation, promotion, and progression. The activator protein-1 (AP-1), an onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…Finally, hydrogenation of alkene 17 provided the proposed cycloinumakiol ( 1 ) in 88 % yield, the structure of which was unambiguously confirmed by 1 H/ 13 C NMR spectroscopy, HRMS, IR spectroscopy, and X‐ray crystallography. While we are confident about our structural characterization of 1 , unfortunately, the NMR spectra of synthetic cycloinumakiol do not match those reported in literature 2. Thus, we anticipated there was a structural misassignment for cycloinumakiol.…”
Section: Methodscontrasting
confidence: 66%
See 2 more Smart Citations
“…Finally, hydrogenation of alkene 17 provided the proposed cycloinumakiol ( 1 ) in 88 % yield, the structure of which was unambiguously confirmed by 1 H/ 13 C NMR spectroscopy, HRMS, IR spectroscopy, and X‐ray crystallography. While we are confident about our structural characterization of 1 , unfortunately, the NMR spectra of synthetic cycloinumakiol do not match those reported in literature 2. Thus, we anticipated there was a structural misassignment for cycloinumakiol.…”
Section: Methodscontrasting
confidence: 66%
“…Previous biological studies of the extracts from the leaves of this plant revealed high antibiotic as well as anticancer activities resulting from inumakiols,1a totarols,1b and other norditerpenes (Figure 1). 1c,d Recently, guided by a bioassay based on activator protein‐1 (AP‐1), the investigation on extracts of podocarpus latifolius at the National Cancer Institute (NCI) led to the isolation of three new inumakiol‐family diterpenes, namely cycloinumakiol ( 1 ), inumakal ( 2 ), and inumakoic acid ( 3 ) 2. The proposed structure of cycloinumakiol ( 1 ) is clearly different from the rest of the tricyclic inumakiol‐family members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of action of nagilactones is multifactorial, as it is frequently the case with natural products. It is not entirely elucidated, but several key pathways have been implicated in the antitumor activity of the most active compounds, essentially Nag-C, Nag-E and Nag-F. About ten years ago, it was shown that Nag-F was able to inhibit activation of the dimeric transcription factor AP-1 (activator protein 1) induced by the phorbol ester TPA (12-O-tetradecanoyl probol-13-ester), with a micromolar efficacy [44]. AP-1, which is in fact a group of transcription factors consisted of four sub-families (Jun, Fos, Maf, and the ATF-activating transcription factors), represents an important modulator in several immune disorders and carcinomas.…”
Section: Molecular Targets and Mechanisms Of Action Of Nagilactonesmentioning
confidence: 99%
“…The intramolecular insertion of olefins into the C1ÀC2 s bond of benzocyclobutenones would lead to benzofused tricycles (Scheme 2 b), which are key motifs in a number of biologically important natural products (Scheme 3). [21] However, there are a number of challenges: 1) achieving the desired regioselectivity is not trivial, because, in general, cleavage of the C1ÀC8 bond of benzocyclobutenones is kinetically favored and therefore catalyzed transformations that involve the cleavage of the C1 À C2 bond remain elusive; 2) the scope of olefins that can undergo carboacylation is often limited. [22] Herein, we describe the development of a rhodium-catalyzed regioselective olefin carboacylation reaction of benzocyclobutenones for rapid access to polyfused rings.…”
mentioning
confidence: 99%